Coping with Sexual Abuse - Romeo, Tameka; Otgaar, Henry; Landström, Sara (UI Scholars Hub, 2018)
General consensus exists in the psychological literature with regard to what constitutes child sexual abuse (CSA) and the negative implications for victims of CSA throughout the course of their lives. Recently, different types of cognitive strategies that victims may use to cope with CSA and the possible effects of these coping strategies on memory have received considerable empirical attention. The first aim of this paper is to provide an overview of the current literature about why, how, and when victims of CSA use the cognitive coping strategies of false denial, disclosure, and recantation to cope with psychological, emotional, and even interpersonal implications of their abuse. Over the years, disclosure is the one strategy that has been researched extensively, whereas research on false denial and recantation has barely just begun. The second aim is to provide a recent overview of the relationship between coping strategies and memory in the context of CSA. Specifically, we will discuss how false denials may have the potential to negatively affect a victim’s memory. Finally, we present an argument for the need to undertake research into insufficiently examined coping strategies such as false denial and recantation.